The Role of Laundry Attendant in Supporting Services at Edelweiss House of Laundry - Novianti, Jenni; Fatimah, Zahara; Lubis, Arina Luthfini (Jurnal Manajemen Pelayanan Hotel, 2024)
Rapid business growth in Indonesia has increased competition, with the main challenge being lengthy and costly licensing processes, as reflected in the Doing Business 2018 rankings. To succeed in the Indonesian market, particularly in the hospitality sector, it is crucial to build strong relationships with both business partners and government entities, as adequate facilities are key to customer satisfaction. On the other hand, the laundry industry is also experiencing rapid growth. Companies in this industry must focus on customer service and the adoption of the latest technology to remain competitive. This study employs a qualitative research method to explore the role and experience of laundry attendants in enhancing service quality, focusing on developing a deeper understanding of their impact on laundry services. Data was collected from primary and secondary sources through observation, interviews, questionnaires, and documentation, and validated using triangulation techniques. The research sample, which is a subset of the population of laundry attendants, was used to draw conclusions that can be generalized to the entire population. The findings indicate that laundry attendants at Edelweiss House of Laundry Batam play a crucial role in maintaining service quality by ensuring that laundry is processed to be clean and fragrant. Their skills and attention to detail significantly affect the final service outcome. The Laundry Manager and Supervisor emphasize the importance of training, supervision, and the use of high-quality chemicals and advanced technology. Service quality evaluation includes the effectiveness of the washing process, handling of customer complaints, and innovations in facilities. Questionnaire results show that customers are satisfied with the appearance, confidence, and speed of service provided by the laundry attendants. This study confirms that the performance of laundry attendants and an efficient service system are key to achieving high-quality standards at Edelweiss House of Laundry Batam.